Enhancing the performance of the domestic refrigerator with hot gas injection to suction line. Issue 1 (April 2016) - Berman, E T; Hasan, S; Mutaufiq,
Abstract: The purpose of this study was to determine the increase in performance of a domestic refrigerator that uses hot gas injection (IHG) to the suction line. The experiment was conducted by flowing refrigerant from the discharge line to the suction line. To get performance data, measurements performed on the liquid brine as cooling load with various temperatures (range from 3°C to – 3°C). The working fluid is used as a cooling medium is R-134a. The experimental results showed that the injection of hot gas to the suction line generates an increase in the coefficient of performance systems (COPs) of 7% and is able to lower the discharge temperature, causing the compressor to work lighter/easier, saving electric power needed by the refrigerator.